Metabolic Matching and Morphofunctional Parameters of Deceased Donor Kidney Transplantation: A Study of Super-Rapid and Delayed Recovery in Asystole Donors (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Deceased donor kidney transplantation is a crucial alternative for patients with end-stage renaldisease lacking living donors. This study aimed to characterize the morphofunctional parameters of post-mortemrenal allograft (RA ex-mortuo) transplantation when modeling super-rapid recovery and delayed recovery fortwo types of asystole donors. Materials and Methods: The study assessed the morphological and histochemicalparameters of RA ex-mortuo under ex vivo conditions in 39 dogs. The morphological analysis involved kidneybiopsies and perfusate examination using light microscopy, morphometric studies, and histostereometric analysis.The study evaluated the height of the renal epithelium in the proximal and distal tubules, the specific volume ofglomeruli in the cortex, and the prevalence of dystrophic changes in the tubular epithelium. Lipid peroxidationproducts in the perfusate were analyzed, and tissue enzyme activity was measured. The study proposed anevaluation algorithm and corresponding criteria to characterize the resource potential of delayed recovery. Theeffectiveness of RA rehabilitation ex-mortuo was evaluated using a scale based on morphological and metabolicdisorder severity. Results: The study pioneered the multicriteria principle to classify asystolic donors as superrapid and delayed recovery, enhancing the understanding of theoretical and practical integration in simulatedreality. Using non-perfusion hypothermia ex vivo for rehabilitating RA ex-mortuo requires 60 min to lower basalmetabolism, as indicated by reduced succinate dehydrogenase and phenoloxidase activity. Early rehabilitationstages showed decreased metabolism, with enzyme activity significantly decreasing at 30 min. Metabolic disorderswere satisfactory at 35 points and mild to severe at 16 points. Conclusion: The activity of key enzymes duringex-mortuo RA rehabilitation showed reduced metabolic processes in both models. Indicators such as AR (−0.09)and AF (0.001%) suggest positive rehabilitation outcomes at both 30 and 120 min, which are closely linked to thetemporal risk factor.